UJI VALIDASI PROTOTIPE SISTEM PREDIKSI PEMBIAYAAN MUSYARAKAH BERBASIS INDIKATOR FDR, DPK, DAN ROA DI BANK SYARIAH - Sumadi; Muqorobin; Tira Nur Fitria (ITB AAS Indonesia Surakarta, 2025)
Prototype musyarakah financing prediction system based on FDR, TPF, and ROA indicators for Islamic banks has undergone testing and validation to ensure functionality and accuracy in a relevant environment. In this study, the system was tested on musyarakah financing prediction using historical financial data from Islamic banks, including key indicators such as the Financing to Deposit Ratio (FDR), Third Party Funds (TPF), and Return on Assets (ROA). The system test results demonstrated a high level of accuracy, with the system capable of producing precise and reliable predictions. This validation provides a strong foundation for the system's implementation to support Islamic bank managerial decisions. The system testing results in the application achieved an excellent accuracy rate of 98.8%. Keywords: Prototype, Prediction, Musyarakah, Website, Financial